"Fear of losing power corrupts those who wield it": the combined effects of leader fear of losing power and competitive climate on leader self-serving behavior. Issue 6 (2nd November 2019) - Wisse, Barbara; Rus, Diana; Keller, Anita C.; Sleebos, Ed
ABSTRACT: Power is generally valued as it offers access to numerous tangible and intangible benefits. Fear of losing it might therefore initiate behavioral responses aimed at capitalizing on those benefits while it is still possible. Therefore, we propose that leaders' fear of losing power may sway them to engage in self-serving behavior. Moreover, we argue that this effect is particularly strong in environments characterized by competition and rivalry, given that such environments foster opportunistic self-interested behavior. The results of two field studies among organizational leaders and their subordinates (one multi-source dyadic study and one multi-source team study) and a scenario experiment show that fear of power loss is positively related to leader self-serving behavior. As predicted, our results show that this relationship is stronger in more competitive organizational climates. We conclude that the potential effects of (anticipated) power loss deserve more research attention than previously awarded.